2019
DOI: 10.1101/766196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERM-Dependent Assembly of T-Cell Receptor Signaling and Co-stimulatory Molecules on Microvilli Prior to Activation

Abstract: T-cell surfaces are covered with microvilli, actin-rich and flexible protrusions. We use super-resolution microscopy to show that 90% T-cell receptor (TCR) complex molecules TCR and TCR, as well as the co-receptor CD4 and the co-stimulatory molecule CD2 reside on microvilli of human T cells. Furthermore, TCR proximal signaling molecules involved in the initial stages of the immune response, such as the protein tyrosine kinase Lck and the key adaptor molecule LAT, are also enriched on microvilli. Notably, p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 95 publications
2
8
0
Order By: Relevance
“…distribution in relation to T cell microvilli was revealed in a recent study using super-resolution microscopic techniques (59). This study showed colocalization of phosphorylated ERM proteins with TCRs and actin filaments in microvilli, suggesting that ERM proteins may stabilize TCR assemblies within microvilli prior to TCR ligand binding and T cell activation (Figure 3A).…”
Section: Erm Proteins In Microvillisupporting
confidence: 63%
See 3 more Smart Citations
“…distribution in relation to T cell microvilli was revealed in a recent study using super-resolution microscopic techniques (59). This study showed colocalization of phosphorylated ERM proteins with TCRs and actin filaments in microvilli, suggesting that ERM proteins may stabilize TCR assemblies within microvilli prior to TCR ligand binding and T cell activation (Figure 3A).…”
Section: Erm Proteins In Microvillisupporting
confidence: 63%
“…Another study using super-resolution optical fluctuation imaging (SOFI) (102) also reported high-density CD4 regions on the surface of Jurkat T cells (101). Haran's group also demonstrated that more than 90% of CD4 and CD2 accumulate on the microvilli of human effector T cells and Jurkat T cells (59). In a 3D superresolution imaging study, CD4 was also reported to accumulate at the microvilli tips, while CD45 was excluded from the tips in unstimulated Jurkat T cells (93).…”
Section: Pre-clustering Of Coreceptors and Proximal Tcr Signaling Mol...mentioning
confidence: 98%
See 2 more Smart Citations
“…[92,93] Upon activation, the microvilli rapidly retract as the T cell spreads out across the surface of an APC. [94] This generates a relatively flat surface with reduced membrane tension and high local concentration of DAG, PI3P, and ubiquitinated TCR. This then leads to recruitment of ESCRT-0 which in turn recruits clathrin and subsequent ESCRT machinery and triggers ectocytic release of TCR-loaded vesicles through CEME.…”
Section: Discussionmentioning
confidence: 99%